Management not models: adaptability, responsiveness, and a few lessons from football - Maclay, Christopher (Development in Practice, 2015)
Despite a swathe of critiques of logframes and other blueprint approaches to development over the last 30 years, most aid infrastructure continues to concentrate on the design and subsequent implementation of closed models. This article does not propose an alternative to blueprints, but challenges the inflexibility of their implementation, which is inadequate given the complex nature of social change. It proposes a supplementary management and learning approach which enables implementers to be dynamic, adaptive, and responsive to problems and opportunities. Emphasising the role of donors, the paper presents a case study of one donor-led programme in Bangladesh doing just this.
_eprint: https://doi.org/10.1080/09614524.2015.983460

Adaptive Programming in Fragile, Conflict and Violence-Affected Settings, What Works and Under What Conditions?: The Case of Pyoe Pin, Myanmar - Christie, Angela; Green, Duncan (Itad, Oxfam and IDS, 2018)
This paper examines adaptive approaches in aid programming in a fragile, conflict and violence-affected setting (FCVAS), namely Myanmar. A combination of desk review and field research has been used to examine some of the assertions around the ‘adaptive management’ approach, which has arisen in recent years as a response to critiques of overly rigid, pre-designed, blue-print and linear project plans. This paper explores if and how adaptive approaches, including rapid learning and planning responses (fast feedback loops and agile programming) are particularly relevant and useful for promoting empowerment and accountability in such ‘messy places’. This case study focuses on Pyoe Pin (‘Young Shoots’), a DFID-funded, British Council managed governance programme, which has been running since 2007.
Keywords: A4EA; Adaptive Development; Economy; Fishery

Making adaptive rigour work - Principles and practices for strenghening monitoring, evaluation and learning for adaptive management - Ramalingam, Ben; Wild, Leni; Buffardi, Anne L (ODI/GLAM, 2019)
Adaptive programmes can be accountable, rigorous and high quality in how they use evidence by taking an ’adaptive rigour’ approach. Core development and humanitarian challenges are complex, and require processes of testing, learning and iteration to find solutions – adaptive management offers one approach for this. Yet large bureaucracies and development organisations can have low tolerance for experimentation and learning, and adaptive management can be viewed as an excuse for ‘making things up as you go along’. This briefing from the Global Learning for Adaptive Management (GLAM) initiative argues that adaptive programmes can be accountable, rigorous and high quality in how they use evidence – but this requires rethinking some key assumptions about how they are practised. The paper sets out three key elements of an ‘adaptive rigour’ approach: - Strengthening the quality of monitoring, evaluation and learning data and systems. - Ensuring appropriate investment in monitoring, evaluation and learning across the programme cycle. - Strengthening capacities and incentives to ensure the effective use of evidence and learning as part of decision-making, leading ultimately to improved effectiveness.

Adaptive Management Practice in the UK Government - The MUVA case - HLS (Human Learning Systems, 2019)
Case study about the MUVA programme in Mozambique. (Maybe it "misses the point of AP which is not learning for learning. Is learning for impact. The word impact doesn’t even come up once!") Adaptive Management programming within the Foreign & Commonwealth Development Office demonstrates that the UK Government has examples of optimising for learning within its existing management practice. However, currently, the adaptive management practices are unhelpfully framed by an approach which limits both their effectiveness and scope. The programmes use learning as their metastrategy. They succeed in connecting practicebased learning with strategic learning, and make a shift towards reframing accountability as accountability for learning. This learning strategy is enabled by funding and contract management arrangements which prioritise learning. Both at macro-level of programme management and micro level of de-risking experimentation and enabling necessary failure by decoupling people’s job security from potential failure.

Top Tips: How to design and manage adaptive programmes - Valters, Craig; Wild, Leni (Overseas Development Institute, 2019)
Within DFID, there is now a commitment to more flexible and adaptive programming. This recognises that: • DFID works in contexts that continuously evolve and change, sometimes in unpredictable ways. To respond to this, the agency needs to remain flexible – to expect change and have a good understanding of context, with resources that can be adjusted and scope to change direction if needed. All DFID programmes should be able to do this. • Some DFID programmes aim to support change in complex systems, behaviours and incentives. Efforts to address women’s empowerment, improve sanitation or build more sustainable health systems, for instance, all require engagement with the way in which complex systems operate and the people and behaviours within them. Trying to deliver reforms in these circumstances is challenging because the pathway to reform itself will be unclear: as a reform is rolled out, the system itself will react and respond. These types of programmes therefore need to build in from the start deliberate processes of learning and testing, to allow for adaptations as more information is gathered for what works over time. These top tips are concerned with programmes that aim to be flexible and adaptive – which work in dynamic contexts and are trying to address complex problems. While there is growing commitment to these approaches, feedback suggests staff still have questions about how to do this well. This document highlights some of the commonly reported issues related to adaptive programming and a set of tips, strategies and examples to help in addressing them. It is aimed at programme managers and advisors who may be Senior Responsible Owners (SROs) or those managing and supporting adaptive programming in a range of ways. We have collated these lessons from discussions with country offices and SROs, feedback from surveys and the wider evidence. We have looked specifically at the adaptive programmes we can find in the DFID portfolio, but this is not an exhaustive list. It should be noted that there is as yet no wide variety of case law to review, but there is a growing set of examples within DFID that can provide continuous learning for the organisation.

Program Cycle - Discussion Note: Managing Monitoring, Evaluation, and Learning Platforms - USAID (USAID, 2018)
This Discussion Note complements ADS 201.3.1.2 Program Cycle Principles by elaborating on Principle 2: Manage Adaptively through Continuous Learning. This Discussion Note is intended for USAID staff interested in learning about recent and promising practices in adaptive management across the Program Cycle.

How to set up and manage an adaptive programme - Lessons from the Action on Climate Today (ACT) Programme - Cooke, Katherine (OPM, 2017)

DFID’s approach to value for money in programme and portfolio management - ICAI (Independent Commission for Aid Impact (ICAI), 2018)
ICAI published this review on DFID’s approach to value for money in February 2018, and as value for money is both a process and an outcome and cuts across all aspects of DFID’s operations, did not score this review. We made five recommendations and published a follow-up to this review in July 2019. All UK government departments are required to achieve value for money in their use of public funds. In recent years, DFID has been working to build value for money considerations further into its management processes and its relationships with implementers and multilateral partners, establishing itself as a global champion on value for money. Review This review was published in February. Though it was not rated, ICAI made five recommendations, and found that the Department for International Development’s approach to value for money was helping to make UK aid spending go further, but improvements are still needed. Findings This review found that DFID has strengthened its processes and systems for ensuring it gains maximum value for each pound spent, has taken swift remedial action to tackle under-performing programmes, and has become a strong global champion on value for money. The review also found that DFID has been diligent in its efforts to cut waste, detect fraud, and improve efficiency, and that this work is improving the return on the UK investment in aid. However, the review found that DFID’s approach was not adequately reporting and capturing results and value for money at the country portfolio level, or how programmes work together to deliver lasting impact, including reducing future dependency on aid. It also found that weakness in the annual review process could undermine DFID’s approach to value for money. It found that targets were frequently revised, and that there could be pressures for optimistic scoring of programmes. Recommendations Based on this review, we made the following five recommendations to help DFID improve its approach to value for money still further: DFID country offices should articulate cross-cutting value for money objectives at the country portfolio level, and should report periodically on progress at that level. Drawing on its experience with introducing adaptive programming, DFID should encourage programmes to experiment with different ways of delivering results more cost-effectively, particularly for more complex programming. DFID should ensure that principles of development effectiveness – such as ensuring partner country leadership, building national capacity and empowering beneficiaries – are more explicit in its value for money approach. Programmes should reflect these principles in their value for money frameworks, and where appropriate incorporate qualitative indicators of progress at that level. DFID should be more explicit about the assumptions underlying the economic case in its business cases, and ensure that these are taken into account in programme monitoring. Delivery plans should specify points in the programme cycle when the economic case should be fully reassessed. Senior responsible owners should also determine whether a reassessment is needed following material changes in the programme, results targets or context. Annual review scores should include an assessment of whether programmes are likely to achieve their intended outcomes in a cost-effective way. DFID should consider introducing further quality assurance into the setting and adjustment of logframe targets.

Contracts for adaptive programming - Bryan, Kevin; Carter, Paddy (ODI, 2016)
Adaptive programming is an approach to development that encourages experimentation, learning & adaptation. This report examines the contractual underpinnings of this approach.

Program Cycle - Discussion Note: Designing Monitoring, Evaluation, and Learning Platforms - USAID (USAID, 2018)
This Discussion Note complements ADS 201.3.1.2 Program Cycle Principles by elaborating on Principle 2: Manage Adaptively through Continuous Learning. This Discussion Note is intended for USAID staff interested in learning about recent and promising practices in adaptive management across the Program Cycle.

How DFID can better manage complexity in development programming - Sharp, Samuel; Valters, Craig; Whitty, Brendan (ODI, 2019)
The United Kingdom’s (UK) Department for International Development (DFID) is an ambitious government department that is committed to reducing poverty and conflict overseas. Many of the issues on which DFID works are complex; whether focused on climate change, gender equality, health or other priorities, simple solutions rarely exist. And to tackle these complex challenges, DFID staff must interact with unpredictable systems of political, organisational and individual behaviours and incentives. There is a risk that complex problems spur more complicated programmes; that the complexity of development challenges is addressed through designing programmes with too many projects and implementers. While there may be valid reasons for this, too many of these complicated programmes will overburden staff. This briefing note is the outcome of an ongoing process within DFID to confront these issues and answer the question: how can DFID design and manage programmes to address complex development challenges without creating too much staff workload? Key messages DFID deals with complex problems, which require flexible systems to support testing, learning and adaptation. • Complex problems do not necessarily require workload-heavy delivery structures, but simpler approaches depend on delivery partners’ experience and competence. • However, programmes that tackle complex problems do require more hands-on engagement and face more workload from inflexible compliance requirements. We suggest that DFID and similar agencies: • Pay closer attention to delivery options in programme design, making use of existing options where possible and, where not, fostering local organisations through long-term investments. • Encourage programme designers to articulate how ambition matches resources and consider ‘good enough’ design. • Reduce the burden of compliance by cultivating partner autonomy, reassessing results and valuefor-money requirements and promoting more flexible contracting and procurement. • Plan and prioritise management resources across a portfolio of programmes to make sure they can be focused in the right areas, where the complexity of the problem requires greater engagement.

DFID’s approach to delivering impact - ICAI (Independent Commission for Aid Impact (ICAI), 2015)
UK aid, at its best, makes a real and positive difference to the lives and livelihoods of poor people around the world. Ensuring the best possible performance across a large and multifaceted aid programme is, however, a complex management challenge. This report reviews ICAI’s previous 44 reports and looks at how well DFID ensures positive, long-term, transformative impact across its work.

Summarising portfolio change: results frameworks at organisational level - Simister, Nigel (Intrac, 2016)

Program Cycle - How-To Note: Strategy-Level Portfolio Review - USAID (USAID PPL, 2017)